New material of Bramatherium grande from the Siwaliks of Pakistan sheds light on dental intra-clade morphological variability of Late Miocene sivatheres. Issue 1 (2nd January 2021) - Khan, Muhammad Akbar; Babar, Muhammad Adeeb; Ríos, Maria
ABSTRACT: Here, we report new dental remains of a large giraffid from the Late Miocene of Pakistan. The new material improves our knowledge of the dental morphology of this extinct sivatherine giraffid, as it sheds light on intra-clade morphological variability within Late Miocene sivatherine giraffids. Fossils were recovered from sediments within the Nagri and Dhok Pathan formations (Middle Siwaliks, Late Miocene) from the sites Nagri, Dhok Pathan, Kauliar and Padhri in Pakistan. Presence of these fossils in Late Miocene sediments in Pakistan demonstrates the stratigraphic range of Bramatherium grande, which was present in the Indo-Pakistani region and the Greco-Iranian region from 11.2 to ca. 3.4 Ma and 11.2 to 9.0 Ma, respectively. The new fossils provide additional data that help resolve the phylogenetic relationships of these large Late Miocene sivatheres. The new findings highlight the presence of Bramatherium grande in the Indo-Pakistani region during the Late Miocene and provide evidence for the synonymy of Bramatherium grande and Bramatherium magnum, with Bramatherium grande having priority.